Evaluation performance of diagnostic methods of intestinal parasitosis in school age children in Ethiopia. (December 2015) - Yimer, Mulat; Hailu, Tadesse; Mulu, Wondemagegn; Abera, Bayeh
Abstract Background Although the sensitivity of Wet mount technique is questionable, it is the major diagnostic technique for routine diagnosis of intestinal parasitosis in Ethiopia. Therefore, the aim of this study was the evaluation performance of diagnostic methods of intestinal parasitosis in school age children in Ethiopia. Methods A cross sectional study was conducted from May to June 2013. Single stool sample was processed for direct, Formol ether concentration (FEC) and Kato Katz methods. The sensitivity and negative predictive value (NPV) of diagnostic tests were calculated in terms of the "Gold" standard method (the combined result of the three methods altogether). Results A total of 422 school age children were participated in this study. The prevalence of intestinal parasites was high (74.6 %) with Kato Katz technique. The sensitivity of Wet mount, FEC and Kato Katz tests against the Gold standard test was 48.9, 63.1 and 93.7 %, respectively. Kato Katz technique revealed a better NPV 80.4 (80.1–80.6) as compared to the Wet mount (33.7 %) and FEC techniques (41.3 %). Conclusion In this study, the Kato Katz technique outperformed the other two methods but the true values for sensitivity, specificity and diagnostic values are not known. Moreover, it is labor intensive and not easily accessible. Hence, it is preferable to use FEC technique to complement the Wet mount test.